Mitral Stenosis Berat pada Penyakit Jantung Rematik - Suwari, Cokorda Istri Padmi; Gede, Widyawati Desak (Faculty of Medicine, Universitas Andalas, 2023)
Rheumatic Heart Disease (RHD) has high morbidity and mortality. Cardiac valve disorders after rheumatic fever are the leading cause of heart failure in children and young adults. A comprehensive understanding of RHD can help early diagnosis and provide optimal management in the future. It has been reported that a 55-year-old man came to the heart clinic of Bhayangkara Hospital Denpasar for routine control of heart disease. The patient has been diagnosed with rheumatic heart disease since 2018. The patient complains of shortness of breath when walking long distances and doing strenuous activities. The patient was diagnosed with CHF FC II ec RHD + MS moderate-severe (Wilkins score 8) + AF NVR (CHA2DS2VASc 3) and treated with heart failure and antiplatelet medication. Mitral stenosis due to RHD produces the typical pathological features seen in Transthoracic echocardiography (TTE), including fibrous thickening and calcification of the valve leaflets, fusion of the commissures, and thickening and shortening of chordae tendineae. Chronic stress overload on the LA due to MS can cause LA dilatation and trigger AF. RHD patients with AF are recommended for anticoagulation for stroke prevention. Patients with acute rheumatic fever clinical features should be evaluated further and given long-term therapy to prevent more severe heart problems.Keywords: Â atrial fibrillation, mitral stenosis, rheumatic Â heart Â disease